The history of protected areas’ network development in the Kharkov region - Atemasova, T. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The main stages of protected areas’ network development in the Kharkov region (Ukraine) have been considered. In the early XX century, the great contribution to the study and protection of valuable natural complexes was made by Society of Nature Study at Kharkov University and Kharkov Society for Naturalists. In the 20–40th years of the XX century outstanding Ukrainian botanists E.M.Lavrenko, M.V.Klokov, S.O.Illichevsky and others carried out studies of typical, rare and unique plant communities. They were employees and correspondents of the Regional Inspectorate of Nature Protection. In 1937 there were established three local reserves in the Kharkov region. In the postwar years, scientists of Kharkiv universities, activists of the Ukrainian Society for Nature Conservation much attention paid to the search and rationale of establishment of the protected areas’ network, and the State Nature Protection Committee, established in 1967, played a significant role. At the beginning of the XXI century due to Ukraine's accession to international agreements, the development of the system of the natural reserve fund has received a new impetus. Today, the system of protected areas of the Kharkov region includes more than 200 territories and objects. The role of legislation for the establishment and development of protested areas’ network is considered. The problems of establishing nature reserves are analyzed.